VLF/LF Reflectivity of the Polar Ionosphere, 3 September - 30 December 1978 - Pagliarulo,Robert P; Turtle,John P; Rasmussen,John E; Cooley,Robert L; Klemetti,Wayne I (1979)
This report provides a summary of high latitude ionospheric reflectivity as observed by the USAF high resolution VLF/LF ionosounder operating in northern Greenland. Ionospheric reflectivity parameters, including reflection heights and coefficients, are presented as a function of time of day. VLF long path propagation measurements, along with magnetometer and riometer data, are presented as supplementary data. (Author)